(untitled) (Itinera, 2017)
The aesthetical experience of the spectator foregrounds on the sense of vision. However in the theatre we more than see, we look at. The performance space becomes the area of the conjunction of gazes, that of spectator and that of artist, the ring of combat for the gaze of the Other. But what if we choose the blindness as the primary point of focus? Influenced by Denis Diderot’s essay Letter on the Blind for the Use of those who can see (1749) the performance Accommodation of Hantu (Pascale Weber and Jean Delsaux) offers a discourse about the gaze and the zone of blindness that surrounds it in the context of the aesthetic experience of the spectator and of the artist.